Business in Africa in the Era of Digital Technology Essays in Honour of Professor William Darley - Abugre, James Baba; L.C. Osabutey, Ellis; P. Sigué, Simon (Advances in Theory and Practice of Emerging Markets, 2021)
XVII, 174 p. 13 illus., 12 illus. in color.